P322 Disease-related worries and concerns in patients with ulcerative colitis: 1-year data from ICONIC. (25th January 2019) - Ghosh, S; Casellas, F; O'Shea, C; Kligys, K; Petersson, J; Peyrin-Biroulet, L
Abstract: Background: ICONIC is the largest ongoing, prospective, multi-country observational study assessing cumulative disease-associated burden in adults with ulcerative colitis (UC) under routine care. This analysis evaluated patient worries and concerns up to 1 year using the Rating Form of inflammatory bowel disease (IBD) Patient Concerns (RFIPC) questionnaire. Methods: Adults with early UC (diagnosed ≤36 months) were enrolled irrespective of treatment regimen or disease severity. Patients completed RFIPC, a 25-item questionnaire comprising frequently reported worries/concerns of IBD patients, at each visit (6-month intervals). Responses are scored on a 10-cm visual analogue scale for each individual question from 0 (no concerns) to 10 (a great deal). The mean of all 25 items represents the total score (lower scores indicate less worries/concerns). In this analysis, data are reported as observed using descriptive statistics at baseline (visit 1 [V1]), month 6 (V2), and month 12 (V3). Patients were stratified by physician-assessed disease severity (mild, moderate, severe, or in remission) at baseline, gender, and geographic location. Results: Mean ± SD total RFIPC scores for all patients were 3.4 ± 2.2 ( n = 1767) at V1, 3.0 ± 2.3 ( n = 1562) at V2, and 3.0 ± 2.3 ( n = 1412) at V3. At V1, mean RFIPC total scores were significantly higher in patients with severe disease vs. patients with mild ( p < 0.0001) or moderate ( p = 0.0174) disease or those in remission ( p < 0.0001). Significant differences in changes from V1 to V3 in mean RFIPC total scores were observed between all disease severity groups ( p < 0.05) except mild vs. in remission; the greatest changes from V1 to V3 were observed in patients with moderate and severe disease at baseline. The disease-related specific concerns with the highest mean total RFIPC scores (ie, scores ≥4.5) for all patients at V1 were 'having an ostomy bag', 'effects of medication', 'uncertain nature of disease', and 'energy level'. Mean total RFIPC scores for these specific concerns decreased over time for all patients. Mean RFIPC total scores at V1 were significantly higher in patients living in Latin America vs. other regions ( p < 0.05) and in males vs. females ( p < 0.0001). However, no significant differences were observed between geographic regions or genders for change from V1 to V3 in total RFIPC scores. Conclusions: Data from ICONIC demonstrated that patients with early UC are highly concerned with the treatment and complications of their disease at all severities of disease, with higher impact among patients with more severe disease. However, these worries decrease over time. Regional and gender differences in UC-related worries/concerns were observed.